Contact Sports as a Risk Factor for Amyotrophic Lateral Sclerosis: A Systematic Review. Issue 1 (February 2019) - Blecher, Ronen; Elliott, Michael A.; Yilmaz, Emre; Dettori, Joseph R.; Oskouian, Rod J.; Patel, Akil; Clarke, Andrew; Hutton, Mike; McGuire, Robert; Dunn, Robert; DeVine, John; Twaddle, Bruce; et al.
Study Design: Systematic review. Introduction: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease, ultimately resulting in paralysis and death. The condition is considered to be caused by a complex interaction between environmental and genetic factors. Although vast genetic research has deciphered many of the molecular factors in ALS pathogenesis, the environmental factors have remained largely unknown. Recent evidence suggests that participation in certain types of sporting activities are associated with increased risk for ALS. Objective: To test the hypothesis that competitive sports at the highest level that involve repetitive concussive head and cervical spinal trauma result in an increased risk of ALS compared with the general population or nonsport controls. Methods: Electronic databases from inception to November 22, 2017 and reference lists of key articles were searched to identify studies meeting inclusion criteria. Results: Sixteen studies met the inclusion criteria. Sports assessed (professional or nonprofessional) included soccer (n = 5), American football (n = 2), basketball (n = 1), cycling (n = 1), marathon or triathlon (n = 1), skating (n = 1), and general sports not specified (n = 11). Soccer and American football were considered sports involving repetitive concussive head and cervical spinal trauma. Professional sports prone to repetitive concussive head and cervical spinal trauma were associated with substantially greater effects (pooled rate ratio [RR] 8.52, 95% CI 5.18-14.0) compared with ( a ) nonprofessional sports prone to repetitive concussive head and cervical spinal trauma (pooled RR 0.60, 95% CI 0.12-3.06); ( b ) professional sports not prone to repetitive head and neck trauma (pooled RR 1.35, 95% CI 0.67-2.71); or ( c ) nonprofessional sports not prone to repetitive concussive head and cervical spinal trauma (pooled RR 1.17, 95% CI 0.79-1.71). Conclusions: Our review suggests that increased susceptibility to ALS is significantly and independently associated with 2 factors: professional sports and sports prone to repetitive concussive head and cervical spinal trauma. Their combination resulted in an additive effect, further increasing this association to ALS.